MEMBUDAYAKAN LITERASI UNTUK MENUMBUHKAN PRIBADI YANG LITERAT TERHADAP LINGKUNGAN DI SMA NEGERI 1 TAMBUN SELATAN - Slamet, Sri Redjeki; Lisasih, Nin Yasmine; Olivia, Fitria; Arianto, Henry; Damayanti, Siti Alfina; Syahputra, Ahmad Reza; Riyadi Sadono, Bayu Ridzki; Wibowo, Randy Yoso; Daryono, Guntur; Lelono, Gatot; Sihotang, Dian Rosalina; Puspita, Ari Isnaeni; Rizqy, Radithya Cahya (Universitas Esa Unggul, 2025)
The community service conducted at SMA Negeri 1 Tambun Selatan was carried out in the form of a Class Literacy Seminar. This activity is conducted to teach students how to read with the aim of improving their literacy skills. The results of the activity show that literacy is an individual's ability to use their skills to process and understand information while participating in activities or tasks that involve reading and writing. Reading ability and reading skills are the foundation for acquiring students' knowledge, skills, and attitudes. that habituating and cultivating students' reading and literacy is part of the effort to foster character or student behavior in accordance with the Minister of Education and Culture Regulation Number 23 of 2015 concerning the Cultivation of Character